Essays on development and regional economics - Alakshendra, Abhinav (Kansas State University, 2012)
The dissertation includes three essays on development and regional economics. Son preference prevails among Indian couples. I test the hypothesis that women who bear sons experience an elevated status within the household, which translates into their increased role in decision-making. The first essay empirically examines the issue. Using data from the Indian Human Development Survey, I find that women who have given birth to at least one son show greater participation in the household’s financial decisions as well as other decisions in a household. Presence of a senior member in the household, however, reduces the women’s relative household bargaining strength. The second essay examines the wage differentials of natives, naturalized citizens, and immigrants on the basis of gender, and for the latter two categories, on the basis of region of origin. This paper argues that the assimilation effect for naturalized citizens should be stronger than that for immigrants since a naturalized citizen, on an average, spends more than 15 years in the country, much higher than immigrants. I find that immigrants experience higher increase in wages than naturalized citizens with longer stay in the United States. The essay concludes that this trend in wages cannot be explained by the assimilation argument alone. We also report that naturalized citizens command higher returns to higher education than immigrants. The third essay explores issues in regional economics. Kansas has the third largest public highway miles and one of the highest miles per person in the country. Due to declining rural population, counties lack the required tax base and fiscal health to support their large ailing rural road infrastructure. The average farm size is increasing and so is the size of vehicles using the rural roads. This paper suggests removing some rural low volume roads from the county road network as one option. I study three Kansas counties to analyze the cost-benefit of reducing low volume road miles. I find that rural counties will be able to save money by closing some low volume roads.
Keywords: Son prefernece; Immigrants; Labor market; Road closure; Economics (0501)